Histological Evaluation of Periapical Tissues after Root Canal Treatment with or without Coronal Seal in Dogs for Six Months - Moazami, Fariborz; Mirhadi, Hossein; Hoseini, Atefeh; Sahebi, Safoora; Torabinejad, Mahmoud (Iranian Endodontic Journal, 2020)
Introduction: Preventing recontamination of the obturated root canal is important for successful root canal treatment (RCT). The main purpose of this study was assessing the histological health of periradicular tissue in obturated root canals with or without coronal seal between two and six months. Methods and Materials: Sixty roots from five dogs with vital pulps were randomly assigned to one of the following five groups (n=12): Group 1, RCT and six months oral exposure; Group 2, RCT and immediate amalgam restoration; Group 3, RCT and amalgam restoration after two months exposure to the oral cavity; Group 4, RCT and amalgam restoration after four months exposure to the oral cavity; Group 5, RCT with two months exposure to oral cavity. The teeth were prepared and filled with gutta-percha and sealer using lateral condensation technique. Two intact root canals of each animal were regarded as the negative control group (n=10), and the two root canals exposed to the oral cavity constituted the positive one (n=10). After six months the animals were euthanized. The upper and lower jaws were removed and submitted for histological processing. Longitudinal sections were obtained from each root. After staining the sections, periradicular regions were examined histologically under light microscope. The Kruskal-Wallis and Mann-Whitney tests was used to analyze the data (P<0.05). Results: The results showed a significant difference between all groups (P<0.05). The negative control group was free of any inflammation. Two-by-two comparison revealed that the positive control group, Group 1 and Group 4 displayed the most intense inflammation. Groups 2, 3 and 5 showed similar results without developing any significant inflammation. Conclusion: Based upon the findings of this animal study, it can be recommended that the obturated root canals which are exposed to oral cavity for around four months or more should be retreated before crown restoration.